Título de la tesis: Aplicación de videojuegos educativos con enfoque constructivista para el aprendizaje de Soporte Técnico para estudiantes de 2° de bachillerato de la Unidad Educativa Primicias de la Cultura de Quito - Guamán Tayupanda, Marco Alfonso (2023)
ABSTRACT: Given the possibilities of video games in the educational field and the lack of this type of resources in specific subjects in the technical area, the present work had the objective of applying educational video games with a constructivist approach for the learning of the Technical Support subject for the second year high school students of the Unidad Educativa Primicias de la Cultura de Quito. The approach was quantitative, with a quasi-experimental, descriptive, and field-based design. For the development of video games, the SUM methodology was used, and they were implemented in Scratch. Three video games were developed, and the final version is available on the web. The sample consisted of 48 students of which the control group had 23 students and the experimental group had 25 students. Survey and test techniques were used, with their respective questionnaires. It is concluded that the use of video games improves student´s performance, as the hypothesis was tested using the t- student test. It is recommended that for the design and development of educational video games an interdisciplinary group of professionals should be considered in order to obtain products that respond to educational needs. Keywords: EDUCATIONAL VIDEO GAME, SUM METHODOLOGY, ICT IN EDUCATION.